2021
DOI: 10.1002/pen.25875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvent on the microstructure of polyvinyl alcohol

Abstract: The method for producing polyvinyl alcohol (PVA) by the solution polymerization of vinyl acetate first and then alcoholysis strategy is industrial. Where solvent plays a vital role in control over stereoregularity, molecular weight and its distribution, crystallinity and so on. In this report, when methyl acetate was used as a solvent in the polymerization of vinyl acetate instead of methanol, prepared PVA was characterized by Fourier-transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This means that saltwater enhances the rigidity of the polymer backbone, and the spatial network structure of the gel is more compact. The comparison of the T g of PVA, AM, and AMPS polymers showed that the T g of polymer gel changed, indicating the miscibility of the polymeric structures. The sharp endothermic peak at 203.83 °C for the gel sample prepared with DI corresponded to the melting.…”
Section: Resultsmentioning
confidence: 99%
“…This means that saltwater enhances the rigidity of the polymer backbone, and the spatial network structure of the gel is more compact. The comparison of the T g of PVA, AM, and AMPS polymers showed that the T g of polymer gel changed, indicating the miscibility of the polymeric structures. The sharp endothermic peak at 203.83 °C for the gel sample prepared with DI corresponded to the melting.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its capacity to undergo pyrolysis at high temperatures, PVA has a melting point of roughly 230 C, hydrolyzes between 180-190 C, and quickly decomposes over 200 C. [16][17][18] Organic coatings, polymeric component, flexible electronics, biomedical devices, and medical technology are just a few of the applications that rely on functional polymer surfaces produced in cutting-edge scientific and technological fields. [19][20][21] Surface modification of polymers can be utilized to improve biological resistance, compatibility or degradability, impact response, thermal stability, multiphase physical response, flexibility, stiffness, and other properties. [22][23][24] According to the literature, the most common PVA modification processes involving hydroxyl groups are esterification, etherification, and acetalization.…”
Section: Introductionmentioning
confidence: 99%